A preliminary study on the potential use of the analytical hierarchical process (AHP) to predict advanced manufacturing technology (AMT) implementation - Yusuff, Rosnah Mohd; Yee, Kok Poh; Hashmi, M.S.J. (Elsevier Science, 2001)
The implementation of advanced manufacturing technology (AMT) requires not only substantial investment in the technology, but also changes in the culture and organizational structure of the organization. It requires careful planning at all levels of the organization to ensure that the implementation will achieve the intended goals. It is a complex process with many factors to be considered before the full benefits of AMT can be realized. A preliminary study on the potential use of the analytical hierarchical process (AHP) has been proposed to help the organizations in planning the AMT implementation process. The AHP method has the ability to structure complex, multi-person, multi-attribute, and multi-period problem hierarchically. Pairwise comparisons of the element (usually, alternatives and attributes) can be established using a scale indicating the strength with which one element dominates another with respect to a higher-level element. This scaling process can then be translated into priority weights (scores). The AMT implementation process has been divided into stages or modules, and each module is independent of the other. Four main modules have been identified-the institutionalization, acceptance, routinization and infusion modules. The factors/elements in each module were identified from the literature and the relative importance for each element established by priority weights. Once the priority weights of the elements/determinants of the module have been calculated, the presence of the corresponding element in the companies will be evaluated. An evaluation rating of these elements multiplied by the established priority weights will determine the prediction weight for the elements and the module. The application of this procedure is described for the institutionalization module, and can be similarly extended to the other AMT implementation modules. By establishing the prediction weight for each module, the companies will be able to evaluate the strength of the corresponding factors present before em barking on the AMT, identify and create awareness of the essential elements in the AMT implementation process and identify the actions necessary before implementing AMT. The AHP can be a useful guide in the decision making process of AMT implementation, especially for small and medium scale industries.